Fertility intentions under the shock conditions: The case of Russian Exodus - Vladimir Kozlov; Ekaterina Sokolova; Olga Veselovskaya; Daria Saitova (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2023)
The paper is devoted to the fertility intentions of the migrants from Russia belonging to the recent wave of so called "Exodus" caused by Russia's invasion in Ukraine in 2022 and its social impact on Russian society. The authors use the disruption hypothesis and predict the drop in the fertility intentions of new-wave Russian migrants in comparison with the old-wave Russian migrants and stayers, matching and controlling for their socio-economic status. Although the new-wave migrants are in the active reproductive age, partnered and in many cases childless, the authors find a strong intention to the fertility postponement and even cancellation among them. The research is based on two on-line surveys organized in April - October 2023 via online social media and by the snowball method. The first survey provided authors with empirical data on old-wave and new-wave migrants, the second one - on stayers, who have close socio-economic characteristics to the migrants. As a result not only the lower birth intentions of the new-wave migrants was observed, but the positive effect on fertility intentions of the subjective income and willingness to stay in the host country. Especially it is obvious for the countries beyond the EU (mainly for post-Soviet and the Balkan ones). On the other hand for the countries of EU (welfare states) the fertility intentions are the highest.
Keywords: D10; J13; J15; J18; 330; Fertility intensions; fertility among migrants; disruption; forced migration; Russian migrants